Penggunaan filter udara berbahan katun untuk meningkatkan efisiensi bahan bakar pada mesin bensin 1500cc - A. Ardiyanta (Universitas Mataram, 2023)
Air filters are an important component of internal combustion engines, especially gasoline engines. The air filter is responsible for filtering dust and dirt particles. The character of the air filter must have good filtering without reducing significantly the quality of the amount of air sucked by the pistons. The purpose of this research, to examine the used of cotton air filters on the average fuel consumption of 1500cc gasoline engine. The research method used experimental research type, with data analysis using a paired sample t-test. Data collection was collected by road tests with variations of mileage, such as 8 km, 100 km, and 120 km. The results of this research found, that with cotton air filters, the average fuel consumption range at 80km was 17.2 km/litre, at 100 km range was 17.7 km/litre, and at 120 km range was 17.4 km/litre. This is better result, while using paper based air filter resulted 80 km at 16,7 km/l, 100 km at 17, km/l, and 120 km at 16,9 km/l. Based on the results of the research, this concluded that the use of cotton air filters affects the average fuel consumption. The use of cotton air filters can increase mileage so that fuel consumption is more efficient.